Immunotherapy Targets in Pediatric Cancer - Orentas, Rimas J.; Lee, Daniel W.; Mackall, Crystal (Frontiers in Oncology, 2012)
Immunotherapy for cancer has shown increasing success and there is ample evidence to expect that progress gleaned in immune targeting of adult tumors can be translated into pediatric oncology. Herein we review first the principles that guide selection of targets for immunotherapy of cancer, emphasizing the similarities and distinctions between oncogene inhibition targets and immune targets. This is followed by a detailed review of molecules expressed by pediatric tumors that are already under study as immune targets or are good candidates for future studies of immune targeting. Distinctions are made between cell surface antigens that can be targeted in an MHC independent manner with antibodies, antibody derivatives or chimeric antigen receptors versus intracellular molecules which must be targeted with T cell therapies rendered in an MHC restricted fashion. Among the most developed immune targets for childhood cancer are CD19 and CD22 on hematologic malignancies, GD2 on solid tumors, and NY-ESO-1 expressed in a majority of synovial sarcomas, but several other molecules reviewed here also have properties which suggest that they too could serve as effective targets for immunotherapy of childhood cancer.